Assessment Of Topographic Variation In UMP Gambang Campus Using Digital Elevation Model (DEM) Data - Muhammad Fazleizam, Mohd Khairudin (2023)
The term topographic refers to documenting and mapping out areas of elevation change, the three-dimensionality of the surface, and the classification of various landforms. To use this term in the modern sense, users must generate Digital Elevation Model data (DEM). The DEM's color representation can be combined with the DEM's topographic details. Topographical features include slope, and the derivatives of slope and aspect, as well as shaded relief. The output image is more based on the image resolution of the topographic features' shape and texture than the DEM alone. A color DEM is commonly combined with a shaded relief image to highlight the topography.